The Role of Korean Civil Societies on the Japanese Comfort Women Issue: The Erecting of Comfort Women Statue Abroad - Liangchoosak, Suchada (Thai Journal of East Asian Studies, 2019)
The aim of this article is to study the role of South Korean civil societies in erecting Korean comfort women statues abroad after the reaching of comfort women agreement on December 28, 2015 between South Korean and Japanese government. The study demonstrates the manner in which the statues were able to be established in different countries, outside South Korea, by investigating 3 groups of South Korean civil societies - the Korean council for women drafted for military sexual slavery by Japan (the Korean Council), Hwaseong city civic group, and Suwon city civic group - that have central role in moving the issue toward international arena to calling for responsibility and sincere apology from Japanese government. This article founds that the erecting Korean comfort women statues abroad was done by South Korean civil societies making transnational network with group of civil society in other country - especially the country that colonized by Japan before and between World War II - and international organizations. In making cooperation with transnational network, South Korean civil societies do it under sisterhood concept and universal ideology – human rights and women’s rights - that have very significant ideology today.